Pendampingan Pengembangan Muatan Karakter Berkebhinekaan Dalam IKM Pembelajaran Matematika Di SDN Ngalang, Gedangsari, Gunungkidul - Sukiyanto; Arcana, I Nyoman; Widyawati, Ani; Kusumaningrum, Betty (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Curriculum development must adapt to the needs and characteristics of student participants according to their time. The launch of independent learning is the start of a driving school program, in addition to the implementation of the independent curriculum. By using teaching tools in learning based on the IKM curriculum, teachers are expected to be able to develop diverse characters in IKM, including local wisdom. The mechanism for implementing activities in general is in the form of planning/preparation, implementation and evaluation. The planning activity is coordinating with the Principal as the giver of permission to carry out Community Service at the SDN Ngalang 1 Gedangsari Gunungkidul school. The implementation of this service uses training and workshop methods. Each implementation stage is accompanied by outcomes whose success can be measured. Meanwhile, evaluation is carried out to measure the success of this activity, namely by providing questionnaires to teachers after the service activity has been carried out. Based on the results of a questionnaire from 17 respondents, it was found that 83% stated that teachers were able to create independent IKM-based Learning designs after this activity took place. Thus, by carrying out this activity, it is hoped that it can develop a content of diverse character in the educational environment and can realize the potential synergy of higher education institutions with partners so that they can develop community service activities.